2014
DOI: 10.1371/journal.pone.0095090
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A Receptor Up-Regulates Retinal Wave Frequency via Starburst Amacrine Cells in the Developing Rat Retina

Abstract: BackgroundDeveloping retinas display retinal waves, the patterned spontaneous activity essential for circuit refinement. During the first postnatal week in rodents, retinal waves are mediated by synaptic transmission between starburst amacrine cells (SACs) and retinal ganglion cells (RGCs). The neuromodulator adenosine is essential for the generation of retinal waves. However, the cellular basis underlying adenosine's regulation of retinal waves remains elusive. Here, we investigated whether and how the adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…Previous reports from us and others show that A 2A R is expressed in the retina, including in microglia (Huang et al, ; Liou et al, ; Madeira, Elvas, et al, ; Vindeirinho, Costa, Correia, Cavadas, & Santos, ; Zhong, Yang, Huang, & Luo, ). The expression of A 2A R has been demonstrated to be upregulated in brain chronic noxious conditions (Cunha, ; Vindeirinho et al, ; Wittendorp, Boddeke, & Biber, ).…”
Section: Discussionmentioning
confidence: 75%
“…Previous reports from us and others show that A 2A R is expressed in the retina, including in microglia (Huang et al, ; Liou et al, ; Madeira, Elvas, et al, ; Vindeirinho, Costa, Correia, Cavadas, & Santos, ; Zhong, Yang, Huang, & Luo, ). The expression of A 2A R has been demonstrated to be upregulated in brain chronic noxious conditions (Cunha, ; Vindeirinho et al, ; Wittendorp, Boddeke, & Biber, ).…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, to promptly increase the PKA activity for SN25b phosphorylation, we applied the A 2A R agonist CGS 21680 (Fig. 3F), shown to enhance A 2A R-cAMP-PKA signaling in retinal neurons (15). We found that overexpression of SN25b in SACs dampened the CGS-induced changes in the fluorescence intensity compared with Ctrl or SN25b-T138A in SACs (Fig.…”
Section: Sn25b Inhibits Synaptic Transmission From Developing Sacs VImentioning
confidence: 81%
“…All procedures were performed in accordance with protocols approved by the institutional animal care and use committees of National Taiwan University. Immunostaining, retinal explant culture and transfection, live Ca 2+ imaging of retinal waves, and whole-cell voltage-clamp recordings were modified from previous studies (7,15). Detailed procedures regarding plasmid information, imaging of SAC exocytosis, in vivo electroporation, anterograde axonal tracing and tissue processing, analysis of the retinogeniculate projection, RT-qPCR, Western blotting, coimmunoprecipitation, and statistics are described in SI Appendix, SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Except for this latter, the other receptors are present in Müller cells, instead astrocytes and microglia cells express all four receptors. The pericytes express A 1 Rs and A 2A Rs, endothelial cells possess A 2A Rs and A 2B Rs, whereas epithelial cells shown all four receptors [Wan et al, ; Wurm et al, ; Li et al, ; Huang et al, ].…”
mentioning
confidence: 99%